Intersectionality in the narratives of black women in computing through the education and workforce pipeline. Issue 3 (12th August 2019) - Yamaguchi, Ryoko; Burge, Jamika D.
Abstract : Purpose: The purpose of this study is to investigate the narratives of 93 Black women in computing in the USA to identify salient themes that are at the intersection of race and gender in the field of computer science. Design/methodology/approach: The study uses a multi-method approach with a survey to describe the sample and a series of focus groups for in-depth analysis of themes. The qualitative methodology uses a grounded theory and consensual qualitative research approach with a research team that includes computer scientists and social scientists to collect and analyze data. Given the highly technical field of computer science and the intersectional experiences of the participants, this approach was optimal to capture and code data through the lens of Black women in computing. Findings: The authors found four main themes that represented specific needs for Black women in the computing community. The first is the importance of linking Black women in computing (i.e. their recruitment, retention and career growth) to the bottom line of organizational and personal accountability. The second is effective cultural and educational supports for Black women in computing across pathways, starting in middle school. The third is to provide leadership development as a part of their educational and workplace experience. The fourth is a collection of empirical research and scholarship about and for Black women as a part of the computing literature. Originality/value: Black women comprise one of the most underrepresented subgroups in the area of computer science in the USA. There is very little research about Black women in computing. To promote broadened participation in computing, there is a critical need to understand the narratives of successful Black women in the space.